(untitled) (Italian Journal of Public Health, 2008)
Background: We can argue that opinions are considered to be part of the physician’s professional identity. Professional identity has been considered a result of learning. After graduation physicians usually continue to study to gain a specialisation, and we can assume that this process affects their opinions because every specialty has its own “cultural climate”. Also, specialists have different views towards the welfare state because, for example, of the fact that they work with different types of population groups. Aim of the study: In this article we will describe how specialists feel about the current level of social security in Finland. Methods: The empirical analysis in our study is based on postal survey. The 2000 working age physicians’ random survey sample was picked from the register of the Finnish Medical Association (n=1092, response rate 54,6 %). The whole questionnaire included questions dealing with social security, health policy and health care system. The data was analysed using means and multinomial logistic regression analysis. Results: This study shows that surgeons and radiologists are the most critical of social security. These groups often think that social security is excessive. In contrast, psychiatrists show a stronger tendency to support social security. All in all, Finnish specialists are more critical of the social security system than are nonspecialised physicians. Conclusions: There are many similarities between Nordic countries when we look at the historical role of medical profession. We can also assume that specialist physicians’ opinions on social security are quite similar compared to those of other Nordic countries.